Association between oxidative balance score and sarcopenia in US adults: NHANES 2011–2018 - Xu, Weihang; Mu, Dongmei; Wang, Yuehui; Wang, Ying; Wang, Changcong; Zhang, Xinyue (Frontiers in Nutrition, 2024)
Abstract Background: Sarcopenia, a condition characterized by diminished skeletal muscle mass, strength, and function, accompanied by inflammation and oxidative stress, remains an area of limited exploration concerning its correlation with the Oxidative Balance Score (OBS). Methods: Leveraging data from the 2011-2018 National Health and Nutrition Examination Survey (NHANES), we meticulously examined sixteen dietary and four lifestyle factors to derive the OBS. Adjusting appendicular skeletal muscle mass (ASM) by body mass index (BMI) served as the designated marker for sarcopenia. To scrutinize the association between OBS and sarcopenia, we conducted weighted logistic regression and engaged in sensitivity analysis. Furthermore, we implemented subgroup analysis and interaction tests to gain comprehensive insights into the relationship across diverse populations. Results: In a sample comprising 6677 individuals aged 20-59, logistic regression illuminated a negative association between OBS and sarcopenia (OR = 0.942 (0.920, 0.964), p <0.001). Robust associations were also discerned between diseases and both dietary and lifestyle OBS. Subgroup analysis unveiled a more pronounced negative association in older, married/living with partner or more educated individuals. Moreover, this association persisted in populations grappling with comorbidities such as hypertension, diabetes, cancer, and arthritis. Conclusions: Our study posits a perceptible link between OBS and the prevalence of sarcopenia among American adults.